1993
DOI: 10.1136/bjsm.27.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Plasma TSH, T3, T4 and cortisol responses to swimming at varying water temperatures.

Abstract: The acute effect of 30-min swimming at a moderate speed, at three water temperatures (20, 26 and 32QC) on plasma thyroid stimulating hormone (TSH), free thyroxine (F.T4), triiodothyronine (T3) and cortisol concentrations was studied in 15 elite male swimmers. Blood was sampled before and immediately after the events. The heart rate, which was continuously monitored during exercise, had the highest response at 320C and the lowest at 20'C. Blood lactate concentrations were found to be similar after the three te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
3
25
1
2
Order By: Relevance
“…Its primary functions are to increase protein breakdown, inhibite glucose uptake and increase lipolysis. The level of serum cortisol is effected by many factor such as intensity, duration and timing of exercise, type of exercise, age, altitude, environmental temperature and psychology (Bernet and Wartofsky, 2000;Deligiannis et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Its primary functions are to increase protein breakdown, inhibite glucose uptake and increase lipolysis. The level of serum cortisol is effected by many factor such as intensity, duration and timing of exercise, type of exercise, age, altitude, environmental temperature and psychology (Bernet and Wartofsky, 2000;Deligiannis et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The free T4 (FT4) athletes had a similar response to TSH, increasing to 20 and 26°C and decreasing to 32°C. Already T3 showed no significant changes after the three sets of exercise [8,9].…”
Section: Thyroid Disorders In Athletesmentioning
confidence: 99%
“…During swimming, the concentrations of cortisol are higher when the environment is hot 98,99) . Dulac et al found that cortisol concentrations in blood were significantly increased during long-distance swimming in cold water 98) . Serum cortisol level increases in response to exercise at moderated altitude [99][100][101] .…”
Section: Environmental Effectsmentioning
confidence: 99%
“…It was shown that thermal stress caused increases in cortisol levels [96][97][98][99] . During swimming, the concentrations of cortisol are higher when the environment is hot 98,99) . Dulac et al found that cortisol concentrations in blood were significantly increased during long-distance swimming in cold water 98) .…”
Section: Environmental Effectsmentioning
confidence: 99%